2020
DOI: 10.21037/apm-20-1273
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and treatment of critically ill patients with COVID-19 in Hebei

Abstract: China. We aimed to clarify the epidemiology, laboratory examinations, imaging findings, and treatment of critically ill patients with COVID-19 in Hebei province, China.Methods: In this retrospective study, the demographic, laboratory and imaging, and treatment data of patients with severe COVID-19 treated in 13 designated hospitals in Hebei were collected and analyzed.Results: A total of 319 severe COVID-19 patients were treated at the 13 designated hospitals between 22 January, 2020 and 25 March, 2020. Eventu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…In this multicenter prospective study, majority of the included patients were male (74.5%), and 40% of the patients were ≥ 65 years, which was consistent with previously published studies 9,10,11,12 . Diabetes mellitus was the most prevalent comorbid condition in our cohort affecting more than half of the patients admitted to the ICU (57.7%), followed by hypertension (53.6%) respectively, while in most reports hypertension was the most prevalent comorbid condition 13,14,15,16,17 . This observation can be explained by the high number of diabetes mellitus cases in our region as the prevalence of Diabetes in adults is 18.3% in Saudi Arabia as a result of the state of urbanization and adopting sedentary lifestyle compared to other countries 18 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this multicenter prospective study, majority of the included patients were male (74.5%), and 40% of the patients were ≥ 65 years, which was consistent with previously published studies 9,10,11,12 . Diabetes mellitus was the most prevalent comorbid condition in our cohort affecting more than half of the patients admitted to the ICU (57.7%), followed by hypertension (53.6%) respectively, while in most reports hypertension was the most prevalent comorbid condition 13,14,15,16,17 . This observation can be explained by the high number of diabetes mellitus cases in our region as the prevalence of Diabetes in adults is 18.3% in Saudi Arabia as a result of the state of urbanization and adopting sedentary lifestyle compared to other countries 18 .…”
Section: Discussionmentioning
confidence: 84%
“…This variation in mortality rate might be attributed different factors such as baseline patient characteristics, different duration of follow up among studies, and different ICU bed availability among different hospitals as a study reported that patient who were admitted to hospitals with lower ICU bed capacity had a higher risk of death 21 . In a previous multicenter cohort study that included 2215 critically ill adults with con rmed 45 , 17 in a study in Wuhan 17 . The median NUTRIC score and SOFA score were 3 and 5, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 104 included studies, mainly observational retrospective, 42 were reporting results from China (19-60), 19 from the U.S.A (61-79), 5 from the U.K (80-84), 24 across Europe, mainly Italy, Spain, France and the Netherlands (85-109), 10 from other countries (110-119) and 3 were international (120-122). All studies reported data on hospitalized patients due to COVID-19 and 35 of them included data for ICU nnnnnn(20, 25, 33, 36, 37, 41, 44, 45, 48, 52, 53, 56, 58, 66, 72, 73, 81-84, 86-89, 95, 96, 98, 101, 103, 106, 107, 109, 111, 119). Eight studies were pediatric (59, 60, 78, 79, 83, 84, 118, 119).…”
Section: Resultsmentioning
confidence: 99%
“…Even in the provinces that were not in close contact with Hubei, the surveillance of imported cases could not be overlooked. Taking Tianjin, Ningxia, and Hebei province as examples, local cases were twice as numerous as imported cases, which was related to several local gathering events of imported cases (Chen et al, 2020;Dong et al, 2020;Zhang et al, 2020b). This study confirms previously described characteristics (Liang et al, 2020;Wu and McGoogan, 2020) and highlights the difference between imported and local cases.…”
Section: Discussionmentioning
confidence: 99%